Water-Smart Agriculture: A biophysical-focused introduction: addressing needs and opportunities - Kueneman, Eric (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
This publication represents a continuation of IICA’s previous commitments and efforts to consolidate and strategically leverage its expertise and partnerships to improve water management in agriculture at multiple levels. Specifically, it represents an advancement from the policy-problem focus of previous series publications on water for agriculture (Water for Agriculture in the Americas, Water Smart Agriculture- Brief) to solution-based approaches at the field level. As this book emphasizes, water smart agriculture and soil management are critical pillars of climate smart agriculture, fundamental for addressing the negative impacts of climate change on smallholder and other farmers. All of us working in the agriculture sector have a great responsibility in using this precious resource efficiently so that we can continue to produce sufficient quantities of nutritious food to feed the world under a changing climate.